2017
DOI: 10.1038/srep40360
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus exploits tunneling nanotubes for cell-to-cell spread

Abstract: Tunneling nanotubes (TNTs) represent a novel route of intercellular communication. While previous work has shown that TNTs facilitate the exchange of viral or prion proteins from infected to naïve cells, it is not clear whether the viral genome is also transferred via this mechanism and further, whether transfer via this route can result in productive replication of the infectious agents in the recipient cell. Here we present evidence that lung epithelial cells are connected by TNTs, and in spite of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(171 citation statements)
references
References 34 publications
(61 reference statements)
7
158
0
Order By: Relevance
“…In this context, recent evidence show that influenza virus potentially exploits TNT networks for transferring viral proteins and the genome from infected to naïve cells (Kumar et al, 2017). Authors argue that influenza uses these networks for evading immune and antiviral defenses and provide an explanation for the propagation of influenza infections and vaccine failures.…”
Section: Resemblance In Dissemination Of Disease Associated Patternsmentioning
confidence: 99%
“…In this context, recent evidence show that influenza virus potentially exploits TNT networks for transferring viral proteins and the genome from infected to naïve cells (Kumar et al, 2017). Authors argue that influenza uses these networks for evading immune and antiviral defenses and provide an explanation for the propagation of influenza infections and vaccine failures.…”
Section: Resemblance In Dissemination Of Disease Associated Patternsmentioning
confidence: 99%
“…Haley et al demonstrated that astrocytes and oligodendrocytes from human brain tissues were negative for LSTc [81]. Therefore, viruses isolated from PML patients with mutations in VP1 within the sialic acid binding sites could possibly lead to neuroinvasion via a sialic acid-independent manner through interactions with an alternate receptor or through a receptor-independent invasion mechanism that has been demonstrated for other viruses [82, 83]. Further research is necessary to define whether viruses with mutations in VP1 are the infectious form of the virus or whether they arise during CNS invasion and contribute to PML pathogenesis through an alternative mechanism.…”
Section: Pml-associated Vp1 Mutationsmentioning
confidence: 99%
“…One difference between the structures concerns cytoskeletal composition. While the initially identified structures were shown to contain actin but not microtubules (Ramírez-Weber and Kornberg, 1999;Rustom et al, 2004;Sowinski et al, 2008;Sartori-Rupp et al, 2019), a number of subsequently identified structures contain microtubules (Önfelt et al, 2006;Gerdes et al, 2013;Osswald et al, 2015;Kumar et al, 2017;Resnik et al, 2018;Kim et al, 2019). Where examined, intermediate filaments have also been identified (Iglič et al, 2007;Ady et al, 2014;Sáenz-de-Santa-María et al, 2017;Resnik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A second difference concerns the size of the structures. TNTs are generally defined as having a diameter less than 500 nm (Rustom et al, 2004;Ariazi et al, 2017;Sartori-Rupp et al, 2019), but other structures can be several microns wide (Vidulescu et al, 2004;Osswald et al, 2015;Kumar et al, 2017). These variations have led to use of additional names such as 'microtubes' to reflect the structural differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation